The legal basis for the use of digital technologies in the registration of rights to natural resources. - Japarkulov, Д.Е.; Gussev, М.А.; Baideldinov, Д.Л. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
Currently, digital technologies and artificial intelligence are increasingly being used in our country to solve public administration issues. One of the tasks of public administration is to control registration activities in the registration of ownership and use rights to natural resources. The current registration procedure is characterized by time costs, paper turnover, corruption risks, and the possibility of falsification of documents. The purpose of this article is to analyze the registration process of registration of real rights to natural resources and formulate proposals for improving this process through the prism of digital transformation. In this study, we have determined that electronic registration is a positive phenomenon that solves many negative issues of the current registration process, simplifying it and making it more open and accessible; however it does not fully satisfy the current needs of society in the field of legal rights registration. The authors of the article substantiate the need to use digital technologies in the registration process through the use of the block chain process.